Jungle Treasure Hunt Board Game: Permainan Edukatif untuk Meningkatkan Durasi Atensi Anak Usia PAUD - Nurani, Mahatma; Salsabila, Maula; Natalie, Helen; Wijaya, Rio; Yulianto, Jony (Bakti Budaya: Jurnal Pengabdian kepada masyarakat, 2024)
School readiness has emerged as one of pressing issues within the context of educational-focused community outreach. Preschool students often have short attention spans and this aﬀects their learning readiness at the elementary level. This issue warrants further intervention and by involving preschool students at TK Tunas Sawo, Sambikerep District, Surabaya, this community outreach program aimed to enhance preschool students’ attention spans. This study developed the Jungle Treasure Hunt Board Game as an intervention tool by combining play-based methods, storytelling, and token economy techniques to 4 preschool students in two consecutive sessions. The processes of community outreach followed the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). In the initial phase, a series of interviews and observations is conducted to assess students and to obtain basic information for the board game development. In the following phase, we worked with students to play board games. What follows is the post-intervention phase, where we conducted evaluation and determined the further action plans. The results showed that the preschool students demonstrated their ability to maintain their attention spans. At the end of the program, the stakeholders and psychologists validated and recommended this board game as an alternative educational tool for maintaining preschool students’ attention spans.